Bacterial screening of apheresis platelets with a rapid test: a 113‐month single center experience. Issue 7 (17th April 2018) - Ruby, Kristen N.; Thomasson, Reggie R.; Szczepiorkowski, Zbigniew M.; Dunbar, Nancy M.
Abstract : BACKGROUND: The 2016 Food and Drug Administration draft guidance describes the use of a rapid test (RT) to enhance platelet transfusion safety and availability. This study reports a 113‐month experience of screening of apheresis platelets (APs) by RT. STUDY DESIGN AND METHODS: From July 2008 to October 2015, all APs underwent an RT on Day 4. Day 6 and 7 units were transfused with transfusion medicine physician approval. Any units remaining on Day 8 had a second RT performed. From November 2015 to November 2017, APs underwent an RT on Day 5 with a repeat RT on Days 6 and 7. During both periods, positive RTs underwent confirmatory testing with culture when repeat testing was positive. RESULTS: A total of 9009 APs underwent an RT on Day 4 or 5. Of these, 45 (0.5%) were RT positive, with no true positives. A total of 754 underwent a second RT on Day 8, with no positives. Since November 2015, 1152 platelets have undergone a second RT on Day 6; 391 have undergone a third RT on Day 7. Of these, five (0.4%) were RT positive on Day 6, with no true positives. There were no septic transfusion reactions identified by passive surveillance at our institution during either study period. CONCLUSION: To date, we have not detected any true positives after performing 11, 306 tests on 9009 APs. A total of 1906 underwent testing twice, and 391 underwent testing three times. We did not identify any conversions from negative to positive on repeat testing.